Teaching Children with Special Learning Needs: A Problem-Solving Approach/Teaching Techniques for Retarded and Pre-Reading Students. (Education Digest, 1967)
Reviews two books. "Teaching Children With Special Learning Needs: A Problem-Solving Approach," by Milton A. Young; "Teaching Techniques for Retarded and Pre-Reading Students," by Mary Lou Durbin.